Molecular Dynamics Investigations of Binding Mechanism for Triazoles Inhibitors to CYP51 - Shi, Na; Zheng, Qingchuan; Zhang, Hongxing (Frontiers in Molecular Biosciences, 2020)
The sterol 14α demethylase enzyme (CYP51) is an important target of fungal infections. However, the molecular mechanism between triazoles inhibitors and CYP51 remains obscure. In this study, we have investigated the binding mechanism and tunnel characteristic upon four triazoles inhibitors with CYP51 based on the molecular docking and molecular dynamics simulations. The results indicate the four inhibitors stabilize in the binding cavity of CYP51 in a similar binding mode. We discover a hydrophobic cavity (F58, Y64, Y118, L121, Y132, L376, S378, S506, S507, and M508) and the hydrophobic interaction is the main driving force for inhibitors binding to CYP51. The long-tailed inhibitors (posaconazole and itraconazole) have stronger binding affinities than short-tailed inhibitors (fluconazole and voriconazole) because long-tailed inhibitors can form more hydrophobic interactions with CYP51. The tunnel 2f is the predominant pathway for inhibitors ingress/egress protein, which is similar to the other works of CYP51. This study could provide the theoretical basis for the development of efficient azoles inhibitors and may lead a better insight into structure-function relationships of CYP51.